Peran Aktif Korban Anak Ditinjau Dari Kajian Filsafat Terhadap Sanksi Pidana Pelaku - Ari Setiani; Selamat Widodo; Suyanto Suyanto (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The phenomenon of children's involvement as victims in criminal offenses, particularly sexual violence and sexual exploitation, has generated debate regarding the relevance of the concept of active victim participation in the imposition of criminal sanctions on offenders. This study aims to philosophically analyze the construction of active child victim participation from a victimological perspective and to examine the legitimacy of its use in sentencing considerations. The research employs a normative juridical method with an interpretive qualitative approach. Data were collected through library research. Data analysis was conducted using a descriptive-analytical method based on victimology, criminal liability theory, and legal philosophy. The findings indicate that child victims who outwardly appear to participate actively are generally situated within unequal power relations, grooming processes, psychological manipulation, emotional dependency, threats, and the influence of the offender's authority. Therefore, the concept of victim precipitation cannot be applied mechanically to child victims due to their limited psychological and moral capacity. The study also reveals that the use of victims' behavior as an implicit factor in sentencing considerations may encourage practices of victim blaming and secondary victimization. From the perspective of legal philosophy, the concept of active child victim participation lacks ethical legitimacy as a basis for reducing an offender's criminal responsibility because it contradicts the principles of moral culpability and child protection.